1995
DOI: 10.1152/jappl.1995.78.3.948
|View full text |Cite
|
Sign up to set email alerts
|

Skin of the dorsal aspect of human hands and fingers possesses an active vasodilator system

Abstract: To test for an active vasodilator system in human hand and finger skin, seven subjects had a small area of dorsal hand, palm, or dorsal finger pretreated with bretylium (BT) to block adrenergic vasoconstriction. Skin blood flow was monitored at a BT-treated site, a comparable untreated site, and the forearm by laser-Doppler flowmetry. Cutaneous vascular conductance (CVC) was evaluated from the ratio of blood flow to arterial pressure. Body cooling, to evaluate vasoconstrictor system blockade, caused CVC at unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 0 publications
2
67
0
Order By: Relevance
“…Previous studies reported that sympathetically-mediated vasoconstriction is evoked in the glabrous skin during cold stress (8,14) and dynamic or isometric exercise (11,18,22). This sympathetically-mediated vasoconstriction in the hand might also be evoked by concentrated finger perception tasks, which in turn contributes to reducing the flow velocity and volume flow of the radial artery.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies reported that sympathetically-mediated vasoconstriction is evoked in the glabrous skin during cold stress (8,14) and dynamic or isometric exercise (11,18,22). This sympathetically-mediated vasoconstriction in the hand might also be evoked by concentrated finger perception tasks, which in turn contributes to reducing the flow velocity and volume flow of the radial artery.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the glabrous skin is innervated by sympathetic adrenergic vasoconstrictor nerves, but lacks influence from active vasodilator nerves (8,9). Previous studies reported that sympathetically-mediated vasoconstriction is evoked in the glabrous skin during cold stress (8,14) and dynamic or isometric exercise (11,18,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects of this study included healthy Japanese women between 25 and 35 y of age. This study was approved by the Ethics Committee of the Kao Corporation in accordance with the principles of the Declaration of Helsinki (Approval number: [13][14][15][16][17][18][19][20][21][22][23][24]. In addition, subjects only participated after receiving a sufficient explanation of the purpose and content of the study and providing informed consent.…”
Section: Methodsmentioning
confidence: 99%